Allelic frequency of 12-FGF4RG and the association between the genotype with number of calcified intervertebral discs visible on radiographs in Coton de Tuléar and French Bulldog breeds - Vilma L. J. Reunanen; Tarja S. Jokinen; Liisa Lilja-Maula; Marjo K. Hytönen; Anu K. Lappalainen (BMC Veterinary Research)
Abstract Background Intervertebral disc disease (IVDD) is a major welfare issue in chondrodystrophic dogs. It is a consequence of chondroid metaplasia of the nucleus pulposus, leading to premature degeneration and calcification of the intervertebral discs (IVDs). Radiographic grading based on the number of calcified discs visible on radiograph (CDVR) between the ages of 24-48 months is an established method for selective breeding against IVDD in dogs. Premature IVD degeneration has a genetic background, and a FGF4 retrogene insertion on chromosome 12 (12-FGF4RG) has been shown to be involved. The aim of this study was to determine the 12-FGF4RG allele frequency and genotype proportions, and the influence of the 12-FGF4RG genotype on number of CDVR in a study population of young adult Coton de Tuléars and French Bulldogs. In this combined prospective and retrospective analytical study, we investigated dogs radiographically screened at 24-48 months of age. The first dataset consisted of 12-FGF4RG genotyping results of 465 Coton de Tuléars and intervertebral disc calcification (IDC) grading results (no, mild, moderate, or severe) for 222 of them. The second dataset included 12-FGF4RG genotypes and IDC grading results (no or severe) of 81 French Bulldogs. Results We observed 12-FGF4RG homozygous, heterozygous and wildtype individuals in both studied breeds. The 12-FGF4RG allele frequencies were also lower than previously reported in the studied breeds and Coton de Tuléars had lower allele frequency (0.35) than French Bulldogs (0.85). The distribution of IDC grading results were 59% no, 16% mild, 9% moderate and 16% severe in Coton de Tuléars and 59% no and 41% severe in French Bulldogs. In both breeds, every copy of the 12-FGF4RG allele significantly increased the risk for a higher number of CDVR, indicating incomplete dominance. Conclusions Our results confirm the significant association between the 12-FGF4RG allele and the number of CDVR and IDC grade in two different chondrodystrophic breeds in age-controlled cohorts of young adult dogs. Our results also suggest that radiographic screening of CDVR and genetic testing of 12-FGF4RG could be used to breed against IVD degeneration predisposing to IVDD.